Wybrane metody klasyfikacji dla dużych baz danych w analizie demograficznego starzenia się ludności w krajach UE i EFTA - Mikulec, Artur (Choosen Clustering Methods for Large Data Sets in Analysis of Population's Ageing in the EU and EFTA Countries, 2009)
In the study, chosen partitioning clustering methods have been discussed - the PAM algorithm (Partitioning Around Medoids) - Kaufman, Rousseeuw and also clustering methods for large data sets, the CLARA algorithm (Clustering LARge Applications) Kaufman, Rousseeuw and the CLARANS algorithm (Clustering Large Applications based on RANndomised Search) - Ng, Han. The PAM and CLARA algorithms were applied to the analysis of population's ageing of society in the EU and EFTA countries. In the calculations, statistics data of population by age at NUTS-2 level for the EU and EFTA countries were applied. Obtained results were compared with results of clustering based on the k-means algorithm (Hartigan-Wong). (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 349-357